ANALISIS PENGARUH FAKTOR KEPUTUSAN PEMBELIAN DENGAN STRUCTURAL EQUATION MODELING PARTIAL LEAST SQUARE - Sukimin Sukimin; Eva Fidriani; Miswaty Miswaty; Juwari Juwari (Fakultas Ekonomi Universitas Balikpapan, 2022)
The purpose of this paper is to idendify the factors affecting consumers’ purchase decision making at Angkringan in Balikpapan. Data were collected by distributing questionnaires to 177Balikpapan consumes who were actively buying food of angkringan. The data were analyzed using the partial least squares structural equation model (PLS-SEM) and multi group analysis (MGA) in SMARTPLS software.. The results show that the product and location have an impact on purchasing decisions. This study illustrates that the determination of product and location are important factors that need to be considered to increase sales due to increased purchasing decisions by consumers. The purchase decision considers the convenience and location that is suitable for buyers to come to the place of business, ease of access and becomes a determinant for buyers and influences buyers' decisions. Suggestions from this study that paying attention to location and product quality will increase purchases.